2019
DOI: 10.1371/journal.pone.0224521
|View full text |Cite
|
Sign up to set email alerts
|

On the development of sleep states in the first weeks of life

Abstract: Human newborns spend up to 18 hours sleeping. The organization of their sleep differs immensely from adult sleep, and its quick maturation and fundamental changes correspond to the rapid cortical development at this age. Manual sleep classification is specifically challenging in this population given major body movements and frequent shifts between vigilance states; in addition various staging criteria co-exist. In the present study we utilized a machine learning approach and investigated how EEG complexity an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…We quantified the 1/f exponent on the 1–20 Hz frequency range and confirmed that it increased with age (age coefficient = 0.26, 95% CI [0.24; 0.27], p<10 –183 , linear model) ( Figure 8C ). A second dataset ( Wielek et al, 2019 ) consisted of EEG recordings from 42 sleeping babies, recorded at 40 and 43 PCW. The analyses revealed that also for these data the PSD slope grew steeper ( Figure 8—figure supplement 1B-C ) and the 1/f exponent increased with age (age coefficient = 0.30, 95% CI [0.17; 0.42], p<10 –4 , linear mixed-effect model) ( Figure 8D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We quantified the 1/f exponent on the 1–20 Hz frequency range and confirmed that it increased with age (age coefficient = 0.26, 95% CI [0.24; 0.27], p<10 –183 , linear model) ( Figure 8C ). A second dataset ( Wielek et al, 2019 ) consisted of EEG recordings from 42 sleeping babies, recorded at 40 and 43 PCW. The analyses revealed that also for these data the PSD slope grew steeper ( Figure 8—figure supplement 1B-C ) and the 1/f exponent increased with age (age coefficient = 0.30, 95% CI [0.17; 0.42], p<10 –4 , linear mixed-effect model) ( Figure 8D ).…”
Section: Resultsmentioning
confidence: 99%
“…To stimulate IN activity, P0-P1 mice from the Dlx5/6-Cre and Gad2-IRES-Cre driver lines were injected in the mPFC with a virus encoding for ChR2 (AAV9-Ef1alpha-DIO-hChR2(ET/TC)-eYFP) as previously described ( Xu et al, 2021 ). Details on the data acquisition and experimental setup of open-access datasets that were used in this project have been previously published ( Chini et al, 2020 ; Bitzenhofer et al, 2021 ; Schetinin and Jakaite, 2017 ; Wielek et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep Diary: Infant daytime sleep duration, Infant no. of night-waking, (Wielek et al, 2019 ) Sleep development 42 (27:15) 2 & 5 weeks old Polysomnography QS/NREM, AS/REM, Wake, Movement time, Transitional sleep, Power spectral density, Entropy measure (Wooding et al, 1990 ) Sleep patterns 874 (432:428) 1–12 months Sleep diary and Questionnaires TST over 24 h, Night-time sleeping, Daytime sleeping, Uninterrupted night sleeping, Sleeping, Waking & Settling times, Bedtime routines (Yoshida et al, 2015 ) Sleep development 34 (17:17) 3 & 4 months Actigraph, EEG, Sleep log Actigraph: Wakefulness, Light sleep, Deep sleep, EEG: Total sleep, Wake, REM, NREM stages 1–2, SWS, No. of sleep cycles (Zhou et al, 2015 ) Sleep development 899 (475:424) 3, 6, 9, 12, 18, & 24 BISQ Avg.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the assessment of what is comfortable and what is not for an individual patient can only be based on close observation of the preterm. In contrast to adults where the sleeping time concentrates on several hours during the night, newborns have irregular sleeping patterns without an established circadian rhythm [65], which makes the organization of an open ward even more challenging. In order to adapt the acoustical environment to each patient's needs, we would need a flexible acoustic environment in each patient zone, which could be realized with advanced acoustic curtains.…”
Section: Characterization Of Environmental Noise At the Nicumentioning
confidence: 99%